Determination of BPJS Employment Membership - Wahyuni, Ummi; Subhan, Subhan; Fathorrahman, Fathorrahman (University Muhammadiyah Aceh, 2025)
This study aims to analyze the influence of knowledge, education, and income on BPJS Employment membership. This study was conducted at the Pamekasan Regency BPJS Employment Office. This study uses primary data through the distribution of questionnaires to 100 Pamekasan Regency BPJS Employment participants. The results of the study indicate that knowledge influences BPJS Employment membership with a significance value of less than 0.001. Education influences BPJS Employment membership with a significance value of less than 0.001. Income influences BPJS Employment membership with a significance value of 0.049. Thus, knowledge, education and income influence BPJS Employment membership